Caracterización de la microbiota en el intestino de Panstrongylus chinai, insecto transmisor de la enfermedad de Chagas en el Sur de Ecuador - Cadena Cárdenas, Matías Leonel (2024)
Chagas disease (CD) is caused by the Trypanosoma cruzi parasite and transmitted mainly by blood-sucking insects of the Triatominae subfamily. This disease is endemic in 21 countries in America, mainly in rural areas, but spreading to urban areas due to human mobility. Ecuador, present an incidence of 36 cases per 100,000 inhabitants per year and 16 species of triatomines were described. Panstrongylus chinai, is an secondary vector in Loja provinces, southern Ecuadorian Region. Insecticides has been used as the main way to control this disease, however, new strategies need to improve to prevent CD. The intestinal microbiota of insects can influence in the transmission of T. cruzi, for that reason the aim of this study is themolecular characterization of the gut bacterial microbiota of Panstrongylus chinai collected in three communities of Loja, Ecuador. For this, i) a total of 63 DUs were examined, of those 5 houses were infested (infestation index = 7.9 %) with 12 individuals of P. chinai. ii) A total 12 samples collected in the DUs and 50 individuals from laboratory colonies were analyzed for the bacterial composition. The intestine and DNA were extracted, performing molecular detection of T. cruzi by PCR and sequencing the bacterial 16S region. The results revealed the presence of T. cruzi in a field sample and the presence of Staphylococcus genus, with the species S. saprophyticus (75%) and S. equorum (25%). This study contributes to the understanding of the microbiota and open for further research to contribute to the control of 77 CD.